The impact of employment and income circumstances on the development of regions - Nagy, János; Harsányi, Gergely; Jánosy, Orsolya; Harsányi, Endre; Nagy, Orsolya (Acta Agraria Debreceniensis, 2014)
The economic condition of an area is fundamentally determined by the extent of employement, as well as the size and composition of its active population. No sustainable economic growth is possible without the necessary amount of employees with the proper skills. As regards the proportion of employees, i.e. economically active people is significanlty lower in Hungary than not only in Western Europe, but also countries which joined the EU recently. One of the reasons for this fact is the low amount of part-time employment and the other is the phenomenon that the number of agricultural employees – who had a significant role – greatly decreased in the county. The employment level of the population in the county is nearly identical as that of the North Great Plain region and it is lower than the country average. The activity proportion, i.e. the joint proportion of employees and unemployed people in the population between 15–74 years of age is 3 percentages lower than the country average. The proportion of unemployed people greatly varies depending on the small regions of the county. The proportion of registered unemployed people in the population of active age is the lowest in Debrecen and the highest in the Hajdúhadház small region. The unemployment of career-starters is a further problem to deal with. The composition of employees in the county is different than the country average. When compared in terms of different economic sectors, it can be observed that agriculture, game management, forestry and fishery are more significant than the country average. Of the provider sectors, the proportion of financial activity, real estate matters and economic services is lower, while that of accommodation services and hospitality is higher than the country average. There are regional differences similar to unemployment in terms of the income size which is the basis of personal income tax per taxpayer. The income level in the North Great Plain region is lower than the country average mainly in terms of income paid for work, where this difference is 23%, while it is only 5% in the case of social income. Altogether, the income and expenditure data of the North Great Plain region are not favourable.